Results of a patient survey for assessment services in renal transplant patients with a history of cancer - Ihrig, Andreas; Maatouk, Imad; Delecluse, Susanne; Pahernik, Sascha; Süsal, Caner; Hohenfellner, Markus; Zeier, Martin; Grüllich, Carsten (Progress in transplantation, 2017)
Patients with cancer who require a kidney transplant often face a prolonged time on the waiting list to ensure a sufficient relapse-free time. Patients and relatives were invited to the patient assessment service where they get an individualized risk assessment and a recommendation for transplantation and waiting period directly from an expert panel. We investigated in 31 patients who filled out questionnaires concerning depression, anxiety, distress, and quality of life and were interviewed for their satisfaction, experiences, and circumstances of the counseling. In 12 (39%) of the 31 patients, a recommendation for transplantation could be made, although the regular waiting period was not yet achieved. The assessment service was received as very good or good by 22 (79%) of 28 patients. We found no relevant differences in patients with regular and shortened waiting time. An interdisciplinary assessment service is a valuable instrument to help with a decision-making between 2 life-threatening conditions.
Gesehen am 11.10.2018